PERAN KEPEMIMPINAN KEPALA DINAS DALAM PEMBENTUKAN BUDAYA KERJA DI KANTOR DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN KUTAI TIMUR - Bayu Aprianto (Jurnal Administrative Reform, 2020)
This study aims to describe the leadership role of the head of the department in shaping the work culture in the Office of the Community and Village Empowerment Office of East Kutai Regency. The results showed that the role of the East Kutai Regency Community and Village Empowerment Agency's role was interpersonal and informational going well. In the role of decision making goes poor.Keywords: Leadership, Work Culture